IMPROVING THE STUDENTSâ€™ VOCABULARY BY USING â€œGO FISHâ€ GAME - Nurman, Moh. (Jo-ELT (Journal of English Language Teaching) Fakultas Pendidikan Bahasa & Seni Prodi Pendidikan Bahasa Inggris IKIP, 2018)
The present study aims at explaining how to improve the studentsâ€™ vocabulary mastery by using â€œGo Fishâ€ game. The study belongs to classroom action research. The participants of the study are one hundred and twenty-two junior high school students of the seventh grade. To measure the improvement of studentsâ€™ vocabulary mastery, the study used test. The finding showed that the mean score, 92,41 in the second Cycle had met the criteria of success. It means that the use of Go Fish game in teaching vocabulary can improve the studentsâ€™ vocabulary mastery.